ANALISIS PENILAIAN PRESTASI KERJA TERHADAP PROMOSI JABATAN KARYAWAN PT. BPRS SARANA PRIMA MANDIRI MEKASAN - Shalehoddin; R.A.Safira Isti Dwi Kurnia (STIE Bakti Bangsa Pamekasan, 2020)
This study aims to determine whether the assessment of work performance has a positive and significant effect on employee promotion. This research was conducted from April to September 2020 at PT. BPRS Sarana Prima Mandiri Pamekasan Head Office. The population in this study were all employees totaling 20 people. The sampling used by this researcher was